Implementasi Program Sinergitas Masyarakat Peduli Panti (SI GEMATI) dalam Perlindungan Lanjut Usia di Panti Pelayanan Sosial Lanjut Usia (PPSLU) Turusgede Rembang Jawa Tengah - Arifah, Syaffa Cinta; Nainggolan, Atirista; Irianti, Decky (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2025)
This research examines the implementation of the Community Synergy for Caring for Nursing Homes Program (SI GEMATI) in protecting older adults at the Elderly Social Service Center (PPSLU) Turusgede, Rembang, Central Java. The program was initiated to address boredom experienced by elderly residents, which is indicated by decreased interest in activities, reduced social engagement, sleep disturbances, anxiety, loneliness, and a lack of enthusiasm for daily routines, ultimately affecting their quality of life. This study focuses on analyzing the organizational structure of the SI GEMATI program, the capacity of human resources, coordination mechanisms, implementers’ understanding, and the program implementation process in providing protection for the elderly. A descriptive qualitative approach was employed. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that although the organizational structure of the SI GEMATI program has been formally established, several challenges persist, including limited human resources, overlapping roles that are not aligned with personnel competencies, suboptimal human resource capacity, ineffective coordination, and limited stakeholder (pentahelix) understanding due to insufficient program socialization. This research recommends several strategic efforts to improve the quality of life of older adults, including strengthening the capacity of SI GEMATI administrators, enhancing collaboration among pentahelix actors (government, community, business sector, academia, and media), increasing program socialization, improving coordination mechanisms, and recruiting additional human resources to reduce overlapping responsibilities.